Determinants of Lake Toba Tourism Selling Value - Ardon Marbun; Juliater Simarmata (Dinasti International Journal of Digital Business Management, 2024)
The scholarly literature review article titled Determining the Sales Value of Lake Toba Tourism is under the domain of marketing management science. The objective of this article is to formulate a hypothesis concerning the correlation between various aspects, with the intention of subsequently utilizing it as a foundation for further investigations within the realm of human resource management. The research employed a descriptive qualitative research methodology. The data utilized in this study is derived from prior research that remains pertinent to the present inquiry. Information was gathered from prominent scholarly online platforms, such as Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results obtained from this study are presented below: 1) Silangit airport service quality on the selling value of Lake Toba tourism; 2) Promotion of tourist attractions on the selling value of Lake Toba tourism; and 3) Accomodation facilities on the selling value of Lake Toba tourism.